Proceso de eliminación de desechos sólidos y su incidencia en la calidad ambiental de la zona alta de la Ciudad de Esmeraldas - Castro Rojas, Dike Eugenio (2016)
The research titled "Process of solid waste disposal and its impact on the environmental quality of the upper area of the city of Esmeraldas, year 2016" was developed in the parish of Esmeraldas, canton and province of the same name, in the neighborhood of San Pedro, Juventud Progresista, Santa Cruz, June 26, and La Terraza, with the general objective of evaluating the incidence of solid waste disposal, which justifies the improvement of the quality of life of the residents; Especially, in the manifestation of changes in social, economic, health and safety. The method used is the hypothetico-deductive, which allowed starting from a hypothesis obtained from the study problem and the relationships among its variables. It was possible to determine that the incidence of solid waste affects negatively the environmental quality of the localities worked. As a result, we applied instruments of measurement of the variables management and environmental quality, as a guide for observation of the management operation, of interview to the population, through which the criterion of citizen perception was obtained, about the management of solid waste and the environmental quality associated with such management, obtaining appropriate and reliable data. In order to evaluate the environmental impact, a matrix was designed and applied that managed and responded to Leopold's methodology. The results obtained demonstrated the validity of the acceptance of the hypothesis, with sufficient confidence verifying the negative predicted influence.